Dietary Salt Reduction: A Glance at India and South Africa - Mushoriwa, Fadzai; Rath, Seema; Mabika, Nomvelo; Bosman, Sean James; Srinivas, Sunitha Chandrasekhar (Indian Journal of Pharmacy Practice)
India and South Africa have a high burden of non-communicable diseases (NCDs), with cardiovascular diseases being the most prevalent. Salt reduction has been identified as a cost effective way of addressing the burden of NCDs such as hypertension and cardiovascular diseases. Salt is introduced into the diet mainly through the consumption of processed foods and discretionary salt that is added during and after cooking. The World Health Organisation recommends 5 g of salt as the adult maximum daily intake. Both the Indian and South African populations, however, have higher intakes. India and South Africa have recognised the need for salt reduction and have taken steps to develop and implement salt reduction initiatives.
Keywords: Salt reduction; Non-communicable diseases; India; South Africa; Sustainable Development Goals